Forgiving Paris [compact disc, unabridged] : a novel - Kingsbury, Karen (Simon & Schuster Audio, 2021)
Ashley Baxter Blake, who made a life-altering mistake in Paris twenty-four years ago, is given a chance at redemption even though she never forgave herself.